A New Technique of Open Septal Reduction Using Polydioxanone Plates for Nasoseptal Fracture: Three-Dimensional Volumetric Analysis. Issue 2 (20th March 2022) - Kim, Kyubeom; Kim, Jaehoon; Kim, Junhyung; Yun, Insik; Jo, Taehee; Choi, Jaehoon; Jeong, Woonhyeok
Abstract : Background: In this study, we designed a new technique for open septal reduction using a polydioxanone (PDS) plate and compared it with closed reduction (CR). Methods: This study included 19 consecutive patients with nasoseptal fracture: 10 receiving open reduction with a PDS plate (PDS group) and 9 undergoing CR group. Open septal reduction was performed after CR for nasal bone fracture. A mucoperichondrial flap was unilaterally elevated, and the deviated septal cartilage was reduced. The PDS plate was inserted horizontally above the vomerine suture. Surgical outcome was analyzed with three-dimensional volumetry and with a quality-of-life scale for nasal obstruction (Nasal Obstruction Symptom Evaluation scale). Results: Complications included 1 case of septal perforation in the CR group and 1 case of PDS exposure and septal hematoma in the PDS group. In the three-dimensional volumetric analysis of the PDS group, the median value of the nasal cavity change significantly differed between 1.14 mL (interquartile range; 0.46–2.4) at the preoperative computed tomography scan and 0.33 mL (interquartile range; −0.22 to 1.29) at the postoperative computed tomography scan ( ∗∗ P  = 0.0039 ) . The Nasal Obstruction Symptom Evaluation scale revealed significant improvement in nasal obstruction postsurgically (median value, 42.5–7.5; ∗ P  = 0.0139) in the PDS group. Conclusions: Polydioxanone plates potentially present a new concept of open septal reduction in terms of septal reinforcement compared with the subtractive approach of open septal reduction.